A new boronic acid based fluorescent reporter for catechol - Wu, Zhongyu; Li, Minyong; Fang, Hao; Wang, Binghe (Bioorganic & medicinal chemistry letters, 2012)
Catechol skeleton widely exists in natural products and bioactive substances. Fluorescent reporters which could recognize catechol are very promising for the construction of chemosensors to detect catechol and its derivatives in biological environment. Herein, we reported a novel catechol reporter, 2-(4-boronophenyl)quinoline-4-carboxylic acid, which exhibits significant fluorescent property changes upon binding catechol containing molecules in an aqueous solution.